Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
:Table of Content • The Reality of Sustainability of Emerging Cybersecurity Companies in Light of Individuals’ Attitudes in Saudi Society Eng. Mohammad Abdulaziz Alduriweesh • The Role of Organizational Citizenship Behavior in Improving Job Quality in (School Feeding and Humanitarian Relief Project (SFHRP) Mr. AbdulKarim Dahan Saleh Ali Al-Hawsli, Prof. Abdulkhaleq Hadi Tawwaf • The Effects of Administrative Corruption in Public Office in The Kingdom of Saudi Arabia Ms. Lina Abdullah Alnafisah , Lecturer Bariah Ibrahim Alyahya • The Impact of Job Loyalty on Employee Job Performance: A Case Study of Almarai Company in the Kingdom of Saudi Arabia Dr. Abdulaziz Mosleh Alharbi • Health status as a mediator variable in the case of factors affecting foreign investment in the KSA Co-Prof. Vivian Mohammad Nasrulddin, Ms. Salwa Murayziq Alsulami • Employment Contracts for Foreign Workers in the Saudi System - A Legal Study of the Saudi Labor System 2025 AD/1446 AH Mr. Maneh Hussein Muhadhal Al-Suqoor • The impact of economic growth on unemployment in Syria during the period (2000-2021) Ms. Loreen Bayan Kshwar